A Dictionary of Chemistry, Vol. III - Macquer, Pierre Joseph (Peter Elmsley, 1777)
The 3rd and final volume of the second English edition of Pierre Joseph Macquer's (1718-1784) Dictionnaire de chymie (1766), translated by James Keir (1735-1820). Macquer's Dictionnaire was one of the most significant chemical dictionaries of the period, containing lengthy descriptions rather than brief definitions. The text was subsequently revised and translated numerous times. Though Macquer is primarily recognized for his Dictionnaire, he also was involved in industrial applications of chemistry such as the development of porcelain, and the use of Prussian blue (ferric ferrocyanide) for dyeing. The dictionary contains more than 500 alphabetical entries, beginning with Acid and ending with Zinc. Translator, Keir, notes deficiencies of the original and first edition English translation in his preface. To address these deficits, Keir added notes, articles, an appendix, and plates to this second edition translation. The plates are intended to more fully describe chemical instrumentation, and the appendix, A Treatise on the various kinds of permanently elastic Fluids, or Gases, (2nd ed.) by Keir, describes discoveries concerning elastic fluids of which Macquer was unfamiliar at the time of the original's publication. The plates and appendix are found following the dictionary entries of this volume.
Keywords: Gases; Chemistry--Dictionaries; Science--Terminology; Chemistry--Study and teaching